2018
DOI: 10.1108/edi-11-2017-0265
|View full text |Cite
|
Sign up to set email alerts
|

Fostering workplace respect in an era of anti-Muslimism and Islamophobia

Abstract: Purpose The marginalization of Muslims can foster anxiety, anger, or fear in the workplace. Such negative reactions may prompt incivility among coworkers, denigrating a thoughtful regard for others. While legal protections are intended to promote fairness, mandates do not always prevent discrimination. As a result, management needs to frame anti-Muslimism as an ethical issue and proactively cultivate environments that support respect. The paper aims to discuss these issues. Design/methodology/approach To und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Most meso-level discriminatory problems in Muslim-minority countries come from the incongruity between organizational and Islamic practices. Studies reported that Muslims face troubles at work because of social networking activities that involve alcohol consumption (Arifeen, 2020;Scott and Franzmann, 2007;Shah and Shaikh, 2010) and difficulty to perform prayers as formally regulated by the organizations (Liao et al, 2017;Lovat et al, 2013;Sekerka and Yacobian, 2018). In addition to the challenges resulted from organizational policy and custom, Muslims in Muslimminority countries also face discrimination from work-related stakeholders like customers, Roles to be performed in the family (e.g., Sakai and Fauzia, 2016) Family discouragement (e.g., Ghasemi, 2013) managers and co-workers.…”
Section: Muslim-minority Countriesmentioning
confidence: 99%
“…Most meso-level discriminatory problems in Muslim-minority countries come from the incongruity between organizational and Islamic practices. Studies reported that Muslims face troubles at work because of social networking activities that involve alcohol consumption (Arifeen, 2020;Scott and Franzmann, 2007;Shah and Shaikh, 2010) and difficulty to perform prayers as formally regulated by the organizations (Liao et al, 2017;Lovat et al, 2013;Sekerka and Yacobian, 2018). In addition to the challenges resulted from organizational policy and custom, Muslims in Muslimminority countries also face discrimination from work-related stakeholders like customers, Roles to be performed in the family (e.g., Sakai and Fauzia, 2016) Family discouragement (e.g., Ghasemi, 2013) managers and co-workers.…”
Section: Muslim-minority Countriesmentioning
confidence: 99%
“…This is possibly not surprising considering how complex individual spirituality can be. Moreover, historical attempts to define spirituality by how it is perceived from an organisational viewpoint have represented a considerable hurdle, which has complicated policy making (Khaled et al 2012;Sekerka, and Yacobian, 2018). Nevertheless, management are missing the opportunity to benefit from positive values and meet the core needs of the workplace by not developing spiritual policies (Mitchell and Beninger, 2015).…”
Section: Limitations/implicationsmentioning
confidence: 99%
“…Their study showed that the perceived view of Muslim workers in their study was that discrimination against them existed within the workplace, whereas in reality employers in the study showed a high level of commitment to respecting the traditions and beliefs of Muslims with little discrimination against Muslim employees being apparent. However, the research by Weller et al (2001) and Vlas (2017), which examined conflict and discrimination in the workplace as reported by members of different ethnic and religious groups, found that Muslims reported the highest level of such incidents, both in terms of the number of respondents indicating that unfair treatment was experienced, and the number reporting these incidents as frequent rather than occasional and the current climate of Islamophobia in many countries has continued to reflect this nearly two decades on (Mahr and Nadeem, 2019;Sekerka and Yacobian, 2018;Ali et al, 2015). Christians on the other hand were generally much less likely to report unfair treatment than Muslims, Sikhs and Hindus, and nearly all the unfairness they reported was occasional rather than frequent, which highlights recent research that echoes the contemporary issues of racial discrimination in the workplace (Wall et al, 2017).…”
Section: Spirituality In the Workplacementioning
confidence: 99%
“…Research has shown that perceived manager respect is important in helping employees identify with their work groups (Al-Atwi, 2018) and that managers should take an active role in creating respectful work environments to avoid incivility and to promote equity and inclusion (Sekerka and Yacobian, 2018). The authors’ practical suggestions for moving forward include experiential education, self-awareness training, and setting expectations for behavior.…”
Section: Promoting Respectful and Appreciative Workplace Environmentsmentioning
confidence: 99%